2022
DOI: 10.6018/turismo.521871
|View full text |Cite
|
Sign up to set email alerts
|

Políticas Públicas Y Overtourism en Destinos Urbanos: Un Análisis Comparado Entre Barcelona Y Palma

Abstract: Overtourism is a growing phenomenon in many destinations that has placed the management of tourist flows among its main challenges. The analysis of the cases of Barcelona and Palma, two cities that stand out among Spanish urban destinations, allows us to review the measures adopted by public administrations to manage this process. The results show the need to move towards integrated tourism governance to improve the management of urban destinations. To this end, a smart tourism planning that also serves to gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…In addition to this figure, there are also the 21 million “passing through” tourists (cruise and excursionists) who only make one-day stops in the city (Bourliataux-Lajoinie, Dosquet, & del Olmo Arriaga, 2019). Gutiérrez, Aguilera, & Ramis (2022) attributed this saturation to three key factors: the strong growth in the supply of tourist accommodation through the proliferation of holiday homes (e.g. Airbnb), the significant development of the cruise industry and the intensification of the pressure exerted by its coastal areas of influence, which are consolidated as major poles of tourist attraction, on an international scale.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this figure, there are also the 21 million “passing through” tourists (cruise and excursionists) who only make one-day stops in the city (Bourliataux-Lajoinie, Dosquet, & del Olmo Arriaga, 2019). Gutiérrez, Aguilera, & Ramis (2022) attributed this saturation to three key factors: the strong growth in the supply of tourist accommodation through the proliferation of holiday homes (e.g. Airbnb), the significant development of the cruise industry and the intensification of the pressure exerted by its coastal areas of influence, which are consolidated as major poles of tourist attraction, on an international scale.…”
Section: Resultsmentioning
confidence: 99%
“…Although destination governance is one of the most decisive aspects in explaining residents' perceptions of touristification and its impacts (Almeida et al, 2019(Almeida et al, , 2021, urban destinations are still far from a model that promotes social participation, and a technocratic approach is prioritised (Picó et al, 2022). Few studies have identified the link between governance characteristics and the intensification of tourism flows (Detotto et al, 2021), and no study has measured the impact of governance on tourism impacts from the perspective of residents.…”
Section: Baggiomentioning
confidence: 99%
“…Other studies have focused on the effects of current urban-tourist dynamics on heritage [41,45]. Finally, studies such as those by Gutiérrez et al [46] have focused on the analysis of public policies in the face of the city's touristification.…”
Section: Tourist Commodification Of Rooftopsmentioning
confidence: 99%